2015
DOI: 10.1007/s10096-015-2407-9
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of Clostridium difficile PCR-ribotype 001 in Slovakia

Abstract: We conclude that C. difficile PCR-ribotype 001 is the predominant PCR-ribotype in Slovakia with a strong potential for clonal spread and development of multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Before the 2016 study, the C. difficile isolates derived from stool samples of patients hospitalized in Slovakia were characterized in three studies performed between 2011 and 2013. All three studies were in agreement and showed a low diversity of ribotypes, except for a predominance of PCR ribotype 001 (60.1%, 85.0%, 70%) (Davies et al, 2016;Nyc et al, 2015;Freeman et al, 2018).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Before the 2016 study, the C. difficile isolates derived from stool samples of patients hospitalized in Slovakia were characterized in three studies performed between 2011 and 2013. All three studies were in agreement and showed a low diversity of ribotypes, except for a predominance of PCR ribotype 001 (60.1%, 85.0%, 70%) (Davies et al, 2016;Nyc et al, 2015;Freeman et al, 2018).…”
Section: Introductionsupporting
confidence: 70%
“…In 2012, two studies reported the ribotyping data of the Slovak C. difficile isolates, and C. difficile ribotypes 027 and/or 176 were not detected (Davies et al, 2016;Nyc et al, 2015). In contrast, ribotype 001 was identified as predominant in four CDI studies within the period 2012 to 2017 (Davies et al, 2016;Nyc et al, 2015;Freeman et al, 2018;Krehelova et al, 2019) and moreover clonal relatedness of ribotype 001 isolates was confirmed in hospital and between hospitals by multilocus variable number tandem repeats analysis and whole-genome sequencing (Nyc et al, 2015;Krehelova et al, 2019;Eyre et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…33 In Germany strains of C. difficile belonging to RT 027 resistant to rifampicin were isolated among patients with osteoarticular infections who were frequently treated with rifampicin. 34 Nyc et al 35 conducted a CDI analysis in 10 academic hospitals in Slovakia by MLVA, testing RT 001 C. difficile fecal isolates of patients from 14 Departments. RT 001, occurred in the years 2007/9 in high percentages in various regions of Europe (Germany, Scotland, Croatia).…”
Section: Dovepressmentioning
confidence: 99%
“…This conclusion is also in line with the conclusions of the above mentioned publications. 28,35,36 C. difficile RT 027 strains are resistant to fluoroquinolones, and possess the MLS B resistance mechanism due to the presence of the ermB gene -multi-drugresistance. 37,38 Among our studied strains, all 29 were resistant to erythromycin (MIC>256µg/mL) and clindamycin (MIC>256µg/mL) and possessed the ermB gene and also were resistant to moxifloxacin.…”
Section: Dovepressmentioning
confidence: 99%
“…This indicated lower antimicrobial resistance levels in countries with a greater C. difficile RT diversity [ 21 ]. In previous CDI studies, RT001 was also identified as predominant in Slovakia [ 22 , 23 ]. The new epidemic strains are less sensitive to antibiotics, e.g., resistant to fluoroquinolones.…”
Section: Discussionmentioning
confidence: 91%